(untitled) (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the place and role of the local history of education in the natural sciences prepare students of secondary school. Determined the structure of local lore knowladge, grounded educational and developmental potencial of the local historical knoeledge in the content of natural sciences.